Digital Democracy Political Participation Through Technology in the Modern Era - Fakhry Amin; Silkania Swarizona; Trihadi Kuncahyo; Yasser Arafat; Riesta Ayu Oktarina (GoAcademica Research & Publishing, 2023)
As a country that upholds democracy, Indonesia uses democracy in carrying out political participation. Along with technological developments, the integration of this technology appears in the way of politics. This research aims to explore the impact of digital technology on political participation in the modern era. In its implementation, this research was carried out using a descriptive qualitative approach. Using relevant data from previous research through literature studies, this research will produce a deeper understanding of the role of technology in shaping the way people engage in politics. The results of this research found that there is a lot of potential in digital democracy technological innovation. These various potentials such as artificial intelligence, blockchain, and mobile devices have the potential to increase the efficiency and quality of political participation. However, in its implementation, there are still several obstacles, such as regulations, ethics, and unequal access to technology. Through the right steps, a more inclusive, transparent, and democratic digital democracy in the digital era can be achieved.